The anomalous Wtb vertex and top-pair production at the LHC - Apurba Tiwari; Sudhir Kumar Gupta (Nuclear Physics B, 2022)
We perform an exclusive study of the anomalous Wtb interaction in the context of LHC. The limits on Wtb anomalous couplings have been estimated via the measurements of the top-quark decay width and cross-section as well as production asymmetries in case the CP is violated. Our investigations reveal that the upper bounds on (|CL|,|CR|) would be of about (1.82, 0.03) ×10−4 at 2.5σ C.L., for the already collected data at the LHC with S=13 TeV for an integrated luminosity of 139 fb−1. The corresponding limits for future hadron colliders, namely, High Luminosity LHC (HL-LHC), High Energy LHC (HE-LHC) and Future Circular Collider (FCC-hh) for the projected luminosities of 3 ab−1, 12 ab−1 and 30 ab−1 are found to be to (0.81,0.006)×10−4, (0.44,0.0017)×10−4 and (0.21,0.0004)×10−4 respectively at 2.5σ C.L.